PENINGKATAN KEDISIPLINAN DAN KUALITAS PEMBELAJARAN GURU PADA MASA PANDEMI COVID-19 MELALUI SUPERVISI AKADEMIK DI SD 009 KUALA TERUSAN PANGKALAN KERINCI - Elfidawati Elfidawati (STKIP Pesisir Selatan, 2020)
The period of the Covid-19 pandemic demands changes to the learning system. Changes in the learning system cause learning activities and monitoring patterns carried out by supervisors to be adjusted to learning during a pandemic. The objectives of this study are 1) to prove whether sustainable academic supervision can improve teacher discipline and teacher quality in managing learning during a pandemic; 2) knowing the right steps in carrying out ongoing academic supervision for learning during the pandemic, and 3) measuring the increase in discipline, learning quality, and quality of teacher learning tools in managing learning during the Covid-19 pandemic qualitatively. This type of research is school action research. The duration of this research was from April 2020 to May 2020. The subjects of this study were class teachers at the 009 Kuala Terusan public elementary school, Pangkalan Kerinci, Riau. The instrument used was the teacher's weekly activity schedule form and the learning device suitability sheet for learning during the pandemic. The results obtained are 1) supervision using the teacher's weekly activity form can improve teacher discipline; 2) supervision during a pandemic, apart from going through observation, also needs to be done by using in-depth discussion techniques with the teacher concerned; and 3) improving the quality of discipline, learning, and learning tools to increase each cycle. So, periodic checks, observations and in-depth discussions are one of the solutions in carrying out supervision during the Covid-19 pandemic.